A Questionnaire-Based Study on the Use of Weight-Loss Medicines and Herbal Mixtures among Pharmacy Students in the Hail Region - Hussein, Weiam Abdul Raheem; Break, Mohammed Khaled Bin; Alafnan, Ahmed; Huwaimel, Bader; Khojali, Weam Mohamed Ali; Khalifa, Nasrin Eldirdiri; Alkefai, Naila Hassan; Osman, Mhdia Elhadi; Alshammari, Ghaliah; Albalawi, Tahani S.; Alshammari, Zahwah; Almutairi, Haya; et al. (Indian Journal of Pharmaceutical Education and Research, 2024)
Objectives: The obesity epidemic continues to grow at an alarming rate because the lifestyle we live plays a big role in the continuation and exacerbation of this problem. The use of medicines and herbs has become widespread, especially among young people. This study's objective was to identify the medicines and herbs used to treat obesity specifically among pharmacy female students in Hail city. Materials and Methods: An online, semi-structured questionnaire was used to collect data, and the resulting information was then statistically analyzed. Results: Obesity problems can be observed among pharmacy female students but at a moderate rate (41%) and most of the participants started showing symptoms of obesity at an early age. About 10% of study participants have an incorrect belief that natural products are better than synthetic ones. Horsetail, green tea extract, and red tea extract were the most extensively utilized herbal extracts for weight loss, according to this study. Liraglutide, Semaglutide, and Orlistat were the most commonly used weight-loss medicines among female students, even though their use was less common than that of herbal combinations. Although a number of the research, respondents used unknown herbal mixtures mostly on the commercial market. Conclusion: This study found that female pharmacy students in the Hail region frequently utilize herbal remedies to lose weight. Therefore, it has become one of the priorities of our upcoming research to try to find out the truth of what is contained in the herbal mixtures used by the students and to reveal their side effects.
Keywords: Obesity; Weight loss medications; Herbal mixtures; Pharmacy Female students; Hail; City